U(‐Th)–Pb age and petrogenesis of Shigar leucogranites, Karakoram Metamorphic Complex, North Pakistan. Issue 10 (1st July 2022) - Awais, Muhammad; Liu, Xiao‐Chi; Qasim, Muhammad; Wu, Fu‐Yuan
Abstract : The Shigar valley of northern Pakistan is a well‐known region for holding a variety of gemstones. As the gemstone‐bearing rock, post‐collisional leucogranites, and pegmatites in Shigar valley have been sporadically researched but the detailed and updated timing record along with the source rocks were not adequate. Here, we present comprehensive U(‐Th)Pb ages, mineral, and whole‐rock isotopic analyses to investigate the petrogenetic evolution of these granitoids. The zircon, xenotime, and monazite U(‐Th)–Pb ages show crystallization of leucogranites that spanned as recent as ~7–3 Ma. The REEs with nearly smooth patterns and distinct negative Eu anomalies in all the leucogranites and pegmatites with contrasting negative Eu anomalies illustrate significantly plagioclase fractionation. These leucogranites and pegmatites have high SiO2 content showing peraluminous geochemistry. Zircon Hf isotopic composition of leucogranites, pegmatites and gneisses have εHf (t) values of −28.4 to +7.4, −24.0 to −16.5, and −13.2 to +1.8, respectively, which shows crustal origin along with the probable contamination from Kohistan‐Ladakh Arc at depths. Furthermore, monazite Nd isotopic composition of leucogranites, pegmatites, and gneisses have εNd (t) values of −22.9 to −9.5, −25.1 to −22.8, and −26.3 to −24.8, which seems purely from crustal source. The whole‐rock Sr‐Nd‐Hf isotopic composition shows that leucogranites and gneisses have 87 Sr/ 86 Sr(i) values of 0.71603 to 0.92518, εNd (t) values of −22.2 to −2.7, and εHf (t) values of −44.1 to −0.2, respectively, that also confines it to the metapelitic origin. Our results overall reveal that the leucogranites are produced mainly by the partial melting of Dassu felsic gneiss from the Karakoram Metamorphic Complex, showing signatures of the upper crustal rocks of the subducting Indian Plate and hybridized juvenile Asian crust. The input of heat for partial melting is likely to be derived either from the lithospheric mantle which followed the slab break‐off or from shear heating along Main Karakoram Thrust. Furthermore, a leucogranite sample yielded a zircon U–Pb age of 84.9 Ma, and monazite U(‐Th)–Pb age of 10.8 Ma. The in‐situ zircon Hf and monazite Nd isotopes yielded εHf (t) values of +3.6 to +10.7, and εNd (t) values of +1.0 to +2.4, whereas the whole‐rock 87 Sr/ 86 Sr(i) value is 0.70522, εNd (t) is +1.1, and εHf (t) is +4.8, respectively, which confirms it to be sourced from the nearby Kohistan‐Ladakh Arc. Abstract : Dassu dome of the Shigar valley and its environs have the youngest leucogranites and pegmatites (~7–3 Ma) intruded into the Karakoram Metamorphic Complex, reflecting the Asian and upper Indian crust as main source, generated after the slab‐break off that led to thrusting and shear heating along the Main Karakoram Thrust. The new development in this study is a sample confirming all the analytical signatures in the favour of Kohistan‐Ladakh Arc, previously mapped in the Karakoram Block.